The blade surface performance and its robotic machining. (31st March 2020) - Qiu, Lei; Qi, Liangtao; Liu, Lanlan; Zhang, Zhu; Xu, Jianwei
Through numerical calculations, it could be found that when the blade surface quality reaches a certain level, the surface quality of the blade was continuously improved, and the guarantee effect on its performance would be weakened. Under this circumstance, continuing to improve the surface quality of the blade had no positive effect on the performance of the blade. Studies had shown that when the blade surface equivalent grit roughness Ks reaches 4.96 (about R a = 0.8 µm), the blade performance was close to the smooth surface of the blade, and no further processing was required to improve the surface roughness. When the surface equivalent grit Ks was greater than 4.96 µm, the surface roughness had a great influence on the blade performance. When Ks was larger than 40 µm, the negative effect is significantly increased. For the different characteristics of the blade and different processing conditions, four kinds of robot-based blade surface grinding schemes were proposed, of which the core content was the robot layout. Based on the robot group's fitting to the spatial surface and the path planning, the experimental verification was carried out.